2013
DOI: 10.11607/jomi.2994
|View full text |Cite
|
Sign up to set email alerts
|

Early-Loaded One-Stage Implants Retaining Mandibular Overdentures by Two Different Mechanisms: 5-Year Results

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…O‐ring systems are the most widely studied attachments. However, this retention system has some problems, such as a greater need of realignment and exchange of the retentive matrix, requiring a greater number of maintenance sessions . Stud attachment types are an alternative treatment option and seem to promote greater comfort by generating greater retention and stability .…”
Section: Discussionmentioning
confidence: 99%
“…O‐ring systems are the most widely studied attachments. However, this retention system has some problems, such as a greater need of realignment and exchange of the retentive matrix, requiring a greater number of maintenance sessions . Stud attachment types are an alternative treatment option and seem to promote greater comfort by generating greater retention and stability .…”
Section: Discussionmentioning
confidence: 99%
“…However, the replacement frequency of the Locator patrix tended to be lower than that of the ball attachment. In a 5-year clinical study of Akça et al,16 the Locator showed less bone resorption and higher plaque and bleeding indices than that of the ball attachment. On the other hand, Krennmair et al17 reported that the satisfaction with the implant overdentures by using the Locator was higher than that of the conventional dentures.…”
Section: Introductionmentioning
confidence: 90%
“…45 Stud attachment types are an alternative treatment option and seem to promote greater comfort by generating greater retention and stability. 45 Stud attachment types are an alternative treatment option and seem to promote greater comfort by generating greater retention and stability.…”
Section: Adjustments 30mentioning
confidence: 99%